2003
DOI: 10.1364/oe.11.003338
|View full text |Cite
|
Sign up to set email alerts
|

Intensity and polarization dependences of the supercontinuum generation in birefringent and highly nonlinear microstructured fibers

Abstract: We present experimental results highlighting the physica mechanism responsible for the initial spectral broadening of femtosecond Ti:Sapphire pulses in a highly birefringent microstructured fiber having a small effective area. By rotating the input polarization and varying the injected power while monitoring the resulting changes in the output spectrum, we are bringing clear evidences that the initial broadening mechanism leading to a broadband supercontinuum is indeed the fission of higher-order solitons into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…An extremely high sensitivity may unavoidably lead to pulse depolarization (e.g., through polarization modulation instability [72] or cross-phase modulation) and invalidate the principal-axis PM capability predicted from the S-GNLSE. To date, the principal-axis PM capability of strongly birefringent fibers has only been justified by the C-GNLSE [73] or experimentally validated [7375] in a rather low nonlinearity ( L NL >5 mm) regime of SC generation.…”
Section: Toward a Practical Coherent Fiber Supercontinuum Lasermentioning
confidence: 99%
“…An extremely high sensitivity may unavoidably lead to pulse depolarization (e.g., through polarization modulation instability [72] or cross-phase modulation) and invalidate the principal-axis PM capability predicted from the S-GNLSE. To date, the principal-axis PM capability of strongly birefringent fibers has only been justified by the C-GNLSE [73] or experimentally validated [7375] in a rather low nonlinearity ( L NL >5 mm) regime of SC generation.…”
Section: Toward a Practical Coherent Fiber Supercontinuum Lasermentioning
confidence: 99%
“…The development of highly nonlinear microstructured fibers (MFs), where the mode fields are tightly confined to an extremely small core and the dispersion can be tailored over a wide range, has enabled researchers to investigate soliton and soliton-related phenomena in new nonlinear regimes. One of the most common applications of MF is to supercontinuum generation [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16], where in the femtosecond regime solitons dynamics plays an important role in the evolution of the spectrum.…”
Section: Introductionmentioning
confidence: 99%
“…Phase matched four-photon parametric mixing [11][12] associated with Raman scattering is the basic mechanism for such spectral broadening, which can be observed even in the normal group velocity dispersion (GVD) regime. Several experiments have demonstrated that the early stage of SC generation is strongly dependent upon the state of polarization of the pumping pulses [13][14][15][16]. It is therefore of particular interest to explore the polarization dynamics of parametric scattering in the holey fibers [17].…”
Section: Introductionmentioning
confidence: 99%